Intracranial vessel wall MRI. Issue 3 (March 2016) - Bhogal, P.; Navaei, E.; Makalanda, H.L.D.; Brouwer, P.A.; Sjöstrand, C.; Mandell, D.M.; Lilja, A.
Abstract : There are many different methods of imaging the intracranial arteries; however, the vast majority of currently used techniques are based on luminal imaging. Although this is useful, it does have limitations as many different pathological processes can produce the same appearance. Therefore, directly imaging the site of the pathology — the vessel wall itself — offers the hope of discriminating between different disease processes. In this review, we will discuss the current status of vessel wall magnetic resonance imaging alongside its potential usefulness in differentiating between various disease entities.